Creekside : An Archaeological Novel - Carmean, Kelli, 1960- (Book collections on Project MUSE., 2010)
In Creekside, dedicated archaeologist Meg Harrington guides her students in a race against time to protect the legacy of the past before bulldozers rip it to shreds. The setting is a Kentucky pasture slated for development--the construction of the new Creekside subdivision. Once, that same beautiful stretch of land was home to three generations who experienced love, loss, and tragedy in their log cabin beside the creek. It was here during the late 18th century that Estelle Mullins struggled to build her home on the dangerous frontier. In Meg's 21st-century world of archaeology we read about excav.